2020
DOI: 10.1177/1750698019900949
|View full text |Cite
|
Sign up to set email alerts
|

Do public speeches induce “collective” forgetting? The Belgian King’s 2012 summer speech as a case study

Abstract: Although social scientists have examined how political speeches may help forge and/or shape collective memories, they have done so with little to no input from psychologists. We address this deficit, demonstrating how a modified version of a well-established and empirically derived psychological phenomenon—socially shared retrieval-induced forgetting—helps explain the mnemonic consequences associated with political speeches, in this case, the Belgian King’s 2012 summer speech. To this end, we analyzed the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…That is, listeners can be motivated to concurrently retrieve for relational reasons. Such relational motives can account for the finding that SSRIF occurs when speaker and listener are members of the same social group, but not when they belong to different social groups (Coman & Hirst, 2015; see also Barber & Mather, 2012;Coman, Stone, Castano, & Hirst, 2014;Stone et al, 2019). Taken together, the extant evidence would suggest that when people listen to a Central Speaker, the speaker should be able to reshape the public's memory through shared practice effects and socially shared retrieval-induced forgetting.…”
Section: Socially Shared Retrieval-induced Forgettingmentioning
confidence: 99%
“…That is, listeners can be motivated to concurrently retrieve for relational reasons. Such relational motives can account for the finding that SSRIF occurs when speaker and listener are members of the same social group, but not when they belong to different social groups (Coman & Hirst, 2015; see also Barber & Mather, 2012;Coman, Stone, Castano, & Hirst, 2014;Stone et al, 2019). Taken together, the extant evidence would suggest that when people listen to a Central Speaker, the speaker should be able to reshape the public's memory through shared practice effects and socially shared retrieval-induced forgetting.…”
Section: Socially Shared Retrieval-induced Forgettingmentioning
confidence: 99%
“…Scholars have previously established an important link between collective memory and well‐being (Walker & Pettigrew, 1984; Zagefka & Brown, 2005). Other research has established that the recollection of collective memories can be influenced by socio‐psychological factors and social events (Sahdra & Ross, 2007; Stone et al., 2020). Yet, how and why collective memory changes in an individual's lifespan are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stone et al. (2020) observed that French‐speaking Belgians recalled less information about the political issues facing Belgium after attending to one of the Belgian King’s biannual speeches. Furthermore, Sahdra and Ross (2007, Study 2) experimentally induced high and low levels of identification with Canada and asked Canadians to freely recollect memories about their country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers have applied a well-known psychological method used to evaluate how particular silences in individual recall can promote forgetting (the method is called retrieval-induced forgetting) in socially shared contexts (Coman et al 2009). Stone et al (2020) even tested this theory in a real-life situation by examining how the omission of particular topics from the speeches of public figures (in this case, the Belgian king) can actively promote collective forgetting.…”
Section: Collective Memory Studies: Across Disciplines and Across Gen...mentioning
confidence: 99%